Visit of Prime Minister Dr. Manmohan Singh to Philippines, January 13-15, 2007. - Manmohan Singh 1932- (Public Diplomacy Division, Ministry of External Affairs, Government of India, 2007)
Transcripts of the speech of Indian prime minister Manmohan Singh, chairman's statements on 5th ASEAN-India Summit and 2nd East Asia Summit, and Cebu Declaration on East Asian Energy Security.